A-35 On-Field Dizziness and Timing of Referral to Vestibular Therapy Following Adolescent Sports-Related Concussion: Initial Findings. (18th June 2020) - Reynolds, E; Covert, K; Bennett, M; Driver, S; King, R; Reynolds, M
Abstract: Objective: To examine if adolescent patients who experienced on-field dizziness immediately following sports-related concussion (SRC) and were referred to vestibular therapy (VT) in 7–9 days returned to play faster when compared to referrals made > 10 days. Method: Registry data for an outpatient clinic specializing in adolescent SRC was analyzed. Of the 85 adolescent patients included, 67 (79%) experienced dizziness immediately following injury; 36 (54%) of which were referred to VT. Mean age at time of injury was 15.3 years; 61.1% were male (n = 22); most were injured while participating in football (38.9%), soccer (16.7%), or wrestling (13.9%). Days to initial VT evaluation from time of injury and days from VT to clearance from concussion protocol were analyzed using a Poisson regression model; age and sex were controlled. Results: Patients referred to VT 7–9 days post-injury returned to play 16 ± 13.4 days earlier (20.7 ± 18.6 days; p < .0001) than patients who received VT 10–20 days post SRC (36.7 days±32). While non-significant, individuals referred to VT > 21 days post-injury returned to play 6 days later than those referred < 10 days (26.3 ± 32.9; p = .14). Conclusions: Appropriate and timely referrals to VT following the presence of on-field dizziness after SRC may play an integral role in recovery, although more research in this area is needed. Initial findings suggest that when determining optimal time frame for referral to VT, 7–9 days post-injury may be most beneficial for adolescents following SRC.